ELT FOR NON-LINGUISTIC FACULTIES: MOTIVATIONAL AND CURRICULAR CHALLENGES IN HIGHER EDUCATION - Halima Mammadova (European Research Materials, 2026)
This paper examines the main difficulties in teaching English to non-linguistic students in higher education. In today’s globalized world, English has become an essential tool for communication in science, education, and professional contexts. However, many students still struggle to achieve an adequate level of proficiency, despite studying English at university. The study discusses key factors affecting learning, including psychological issues such as low motivation and lack of confidence, methodological challenges like limited classroom hours and insufficient practice, and physical factors including a heavy academic workload. It also addresses issues such as first language interference, concentration problems caused by mobile phone use, and difficulties in vocabulary acquisition. The paper emphasizes the importance of creating a supportive classroom environment and applying effective teaching methods to enhance student engagement and performance. Overall, it argues that improved teaching strategies and stronger learner motivation can significantly enhance English learning outcomes for non-linguistic students.